Aplicativos computacionais para o ensino de matemática - SILVA, Wilton Cesar Nascimento da (2019)
This work is to develop a computer application in the Java programming language to support the teaching of mathematics. Related works are described in the text. As an example, are summarized the functionality of the software. Examples are comments on how the teacher could use the software in the teaching of mathematics. Then appears the software requirement specification Sispemath - System for teaching mathematics, and a brief specification and design analysis and descriptions of the features of the system. There are examples and comments from the use of Sispemath informing the user details of use. The Java code of the prototype is found in Appendix A.